The lex mercatoria in theory and practice - Toth, Orsolya, 1981 February 26- (Oxford, United Kingdom : Oxford University Press, 2017)
This title analyses the 'law merchant', clarifies current thinking and includes a formula to recognise and apply a rule of the lex mercatoria in practice
Lex mercatoria : the debate as it currently stands -- The existing accounts of the lex mercatoria -- Framework for an analytical account : clarifying Terminology -- Framework for an analytical account : the 'Autonomous' status of the lex mercatoria -- A rule of the lex mercatoria : opening the debate to public international law -- A rule of the lex mercatoria : opening the debate to jurisprudence -- The lex mercatoria as a legal system -- Conflicts recognition of the lex mercatoria : the status quo -- Conflicts recognition of the lex mercatoria : the proposed model -- Substantive recognition of the lex mercatoria
BIBINDX
Keywords: Arbitration and award; Commercial law; International commercial arbitration; Electronic books